Corner of burn in section 26 - Sprague, Sallie, photographer (Colorado State University. Libraries, 2008)
Corner of greened up burned area surrounded by brown grasses in unburned SGS, section 26, no cattle.
Keywords: vegetation; SGS; experiments; landscapes